Absent animals in Patrick Deville's Kampuchéa - Epp, Marla (My University, 2023)
This article focuses on the ways in which encounters with animals, a frequent trope in travel literature, are reworked in Patrick Deville's Kampuchéa (2011) to reflect the current dire ecological situation. Deville's narrator is in South East Asia following the path of French naturalist Henri Mouhot, whose diary of his travels was published in 1868. Although the travel routes are similar and the basic components of a travel narrative remain, Mouhot's literary style is reconfigured to reflect the twenty-first-century traveller's awareness of the violent past of the region and anxiety over the future of the planet. If animals abound in Mouhot's diary, they are remarkable in Kampuchéa primarily through their absence. Deville does not, however, occlude them from his narrative, but rather writes about them in absentia. This article studies the implications of Deville's writing about animals without any meaningful face-to-face encounters. It further considers the repercussions of these lost moments of exchange and argues that Deville's commitment to writing about animals, even those who are absent, works to keep their looming extinction at the forefront of readers' minds.
Keywords: travel narratives; animal extinction